Preparing teachers for the use of digital technologies in their teaching practice - Vasileios Dagdilelis (Research in Social Sciences and Technology, 2018)
Greece these last 15 years has developed and implemented a large-scale system for the integration of digital technologies in education and more specifically in the teaching practice. "Large-scale" means that the whole program concerns all Greek education system. A very important part of this nationwide project is the training of teachers program that involves practically all Greek teachers - so far more than 120,000 teachers have been involved and soon they will be involved all of them (approximately 150.000). In this paper we present a summary of this plan. The monitoring of this project at national level, almost from its very beginning, gave to us the opportunity of collecting a large volume of raw information and data of both quantitative and qualitative nature.